Pengaruh Teknik Distraksi Terhadap Penurunan Suara-Suara Pada Pasien Halusinasi Pendengaran di Yayasan Rumah Ceria Repok Tahun 2022 - Silvia Sri Devi; Marisca Agustina; Ruswanti Ruswanti (Lembaga Pengembangan Kinerja Dosen, 2023)
Background: Auditory hallucinations are a symptom that often appears in schizophrenia sufferers. Distraction techniques in nursing interventions to divert attention to what is being presented. This distraction technique is very influential for individuals with mental disorders, especially those who experience auditory hallucinations. Objective: To determine the effect of distraction techniques on patients with auditory hallucinations. Method: This research uses a quasi-experimental research design with a one group pre-post-test design approach and non-probability sampling techniques with a purposive sampling model. Results: This research found that 4 respondents experienced moderate hallucinations (26.7%), respondents with the criteria of experiencing severe hallucinations as many as 6 respondents (40%), and very severe hallucinations as many as 5 respondents (33.3%). After being given the treatment of conversing with other people, 7 respondents (46.7%) experienced a decrease in their voices, namely they became mild, and 8 respondents (53.3%) experienced a decrease in their voices to moderate. Conclusion: There is an effect distraction technique to reduce voices in patients with auditory hallucinations based on the results of data processing using the paired T-Test.